1997
DOI: 10.1002/art.1780401013
|View full text |Cite
|
Sign up to set email alerts
|

Increased nitric oxide production accompanied by the up‐regulation of inducible nitric oxide synthase in vascular endothelium from patients with systemic lupus erythematosus

Abstract: Objective. To investigate whether systemic lupus erythematosus (SLE) is accompanied by increased serum nitrite levels, whether active compared with inactive disease is associated with greater nitric oxide (NO) production, and whether endothelial cells or keratinocytes serve as cellular sources of NO by virtue of their increased expression of either constitutive nitric oxide synthase (cNOS) or inducible NOS (iNOS).Methods. Fifty-one serum samples (46 from patients with SLE) were analyzed for NO production by me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
81
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(92 citation statements)
references
References 25 publications
9
81
0
2
Order By: Relevance
“…NO mediates DNA damage by three mechanisms. It has been reported that NO production is increased in patients with Systemic lupus erythematosus (SLE) [31]. The disorder is characterized by immune activated state where Inducible nitric oxide synthase (iNOS) level is increased in tissues like macrophages, splenic and renal tissues and consequently NO production [32].…”
Section: Direct Effect Of Nomentioning
confidence: 99%
“…NO mediates DNA damage by three mechanisms. It has been reported that NO production is increased in patients with Systemic lupus erythematosus (SLE) [31]. The disorder is characterized by immune activated state where Inducible nitric oxide synthase (iNOS) level is increased in tissues like macrophages, splenic and renal tissues and consequently NO production [32].…”
Section: Direct Effect Of Nomentioning
confidence: 99%
“…However, MRL/lpr iNOS knockout mice develop renal disease similar to the wild-type animal [64]. Belmont and colleagues reported elevated serum nitrite levels, an in vivo marker of NO production, in lupus patients [65,66]. Serum nitrite levels correlated with disease activity and anti-DNA antibody levels.…”
Section: Nitric Oxide Induced Mitochondrial Biogenesis Mediated Altermentioning
confidence: 99%
“…Nitric oxide synthesised by endothelial nitric oxide synthase (eNOS) has vasodilatory effects on vascular tone, inhibits platelet aggregation, and modulates smooth muscle proliferation [10]. Overproduction of NO could contribute to tissue injury, given its capacity to increase vascular permeability, generate toxic free radicals, such as peroxynitrite, and induce cytotoxicity [11]. Deficiency of the NOS3 gene leads to reduced bone formation and impaired osteoblast function [12].…”
Section: Introductionmentioning
confidence: 99%